PENGARUH SUBSTITUSI JANTUNG PISANG TERHADAP KUALITAS ABON DAGING SAPI - Fiannisa, Resti; Faridah, Anni; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was distributed by the utilization of banana heart is still not varied and prices of beef abon is expensive. This research aims to analyze the influence of substitution banana heart as much as 0%; 25%; 50% and 75% of the quality beef abon in terms of color, smell, taste and texture. This type of research is pure experiment using the method of complete random design with three repetition. The type of the data used is the primary data sourced from 30 panelists who gave the answer to the question form (format organoleptic). The data already obtained later is tabulated in the form of tables and the analysis Variant (ANAVA). If different test followed by Duncan. Results of the research showed there was significant influence of the quality beef abon that is brown color quality, taste banana heart quality and fibrous fiber quality but has no effect on the good smell quality, savory taste quality and crisp texture quality. It can be concluded that the best percentage is found on substitution banana heart as much as 75%.Keywords : Banana Heart, Beef Abon, Quality.